Asmaul Husna mobile application (AHMA): foundation of the prototype design and development / Arifah Fasha Rosmani, Ariffin Abdul Mutalib and Siti Mahfuzah Sarif - Rosmani, Arifah Fasha; Abdul Mutalib, Ariffin; Sarif, Siti Mahfuzah (UiTM Cawangan Perlis, 2021)
Asmaul Husna Mobile Application (AHMA) is a prototype mobile application based on an interaction model intended for use in heutagogy with undergraduates. This app was created and designed to increase students' knowledge, perceived awareness, and perceived motivation for the learning material. When learners are assisted with signalling or cueing to focus their attention on the most appropriate resources, they demonstrate improved learning performance and significantly reduced cognitive load. The signalling principle's effectiveness in enhancing learning outcomes by emphasising correspondences between text and images has been increasingly confirmed by empirical research. AHMA's heutagogic design encourages students to explore, connect, and reflect through their self-learning process. By promoting aspects of the learning experience that are conducive to lecture or self-paced learning. This project involved a four-phase methodology which includes planning, design, development, and evaluation. According to the pre-and post-testing and heuristic evaluation results, AHMA significantly improved the learning experience and user interaction in a mobile learning environment.